When Architecture Meets Activism : the Transformative Experience of Hank Williams Village in the Windy City. - Guy, Roger (Lexington Books, 2016)
This social history and community study documents the events surrounding the attempt by community members, activists, and VISTA architects to resist the planned construction of a community college in the neighborhood of Uptown. Due to the brief and obscure nature of these events, this is some of the only surviving material that documents the Hank Williams Village project.